IKLAN : PRODUK BUDAYA POP YANG MENELIKUNG PEREMPUAN - Perwita, Alvika Hening (KOMUNITAS)
Series of ads that appear in printed media, electronic, and internet diverse increasingly and of course we can not deny its existence. Most of the advertising icon is using the profile of women as an object. Even women icon sometimes is displayed only and no links/ anything to do with the product being advertised. Overall the product ads directly related to women are aimed to attract attention, exploit the female body, degrade women, and even provide examples of sexual harassment. Besides those cases, women also made the largest consumer advertising products. And the most pitiful representation of women in the ads, which portrayals of women in the ads are always, sought perfection and automatically it will present camouflage to the real world of women. The fact that popular culture products capable of twisted woman was already familiar to the public. Therefore, we require a study that could uphold women. There was a study which until now has not been reviewed by a group of feminism, which is about the strength of women. This study said that woman must be held to prove that she was able to exist in the lives of men and the growing popular culture products.